Direito e religião : os casos do matrimônio, adoção e escravidão no padroado e na tentativa de criação do primeiro código civil brasileiro, no período de 1822 a 1916 - Bandeira, Walério Magalhães (2021)
The present research aimed to study "Law and Religion: the cases of marriage, adoption and slavery in the Patronage and in the attempt to create the first Brazilian Civil Code in the period from 1822 to 1916". As a general objective, it was intended to propose the analysis of situations in which the principle of human dignity was not observed, concentrating as a space the nascent Brazil, in the temporal delimitation from 1822 to 1916, that is, from the Proclamation of Independence to the effective delivery of the Civil Code to the Brazilian people, after 94 years. The specific objectives were: a) To analyze the influence of the Padroado on the formation and structure of the Brazilian State, starting with the study of its origin in Portugal, its influence on the national civil legal system, as well as the relationship of the Church with the slavery system and with the enslaved as a human person; b) Analyze the institute of marriage as the only form of constitution of a legally supported family and the development of the institute of marriage in the period covered in the research, as well as on the marriage performed by a religious leader as the only valid form in the times of Empire Brazil; c) To analyze the situation of children and adolescents who lived outside the family structure legally constituted at the time by marriage, focusing on the study of the development of the adoption institute in the time frame object of the study; d) finally, discuss the unsuccessful attempt by Teixeira de Freitas to draw up the first Civil Code in the period of Imperial Brazil, given the reality of slavery and his attempt to omit this fact in the aforementioned legal diploma, suggesting the creation of a "Black Code" aside. The method used was the hypothetical-deductive, guided by a theoretical bibliographic and documental framework, comparative study and discourse analysis. It was concluded that, despite social advances, Brazil has always been under the interests of elites that alternate in power, and that sometimes made their particular interests prevail over the interests of the community